Reactive oxidative species-modulated Ca2+ release regulates β2 integrin activation on CD4+ CD28null T cells of acute coronary syndrome patients - Samstag, Yvonne; Bogert, Nicolai; Wabnitz, Guido H.; Din, Shabana; Therre, Markus; Leuschner, Florian; Katus, Hugo; Konstandin, Mathias (The journal of immunology, 2020)
The number and activity of T cell subsets in the atherosclerotic plaques are critical for the prognosis of patients with acute coronary syndrome. β2 Integrin activation is pivotal for T cell recruitment and correlates with future cardiac events. Despite this knowledge, differential regulation of adhesiveness in T cell subsets has not been explored yet. In this study, we show that in human T cells, SDF-1α-mediated β2 integrin activation is driven by a, so far, not-described reactive oxidative species (ROS)-regulated calcium influx. Furthermore, we show that CD4+CD28null T cells represent a highly reactive subset showing 25-fold stronger β2 integrin activation upon SDF-1α stimulation compared with CD28+ T cells. Interestingly, ROS-dependent Ca release was much more prevalent in the pathogenetically pivotal CD28null subset compared with the CD28+ T cells, whereas the established mediators of the classical pathways for β2 integrin activation (PKC, PI3K, and PLC) were similarly activated in both T cell subsets. Thus, interference with the calcium flux attenuates spontaneous adhesion of CD28null T cells from acute coronary syndrome patients, and calcium ionophores abolished the observed differences in the adhesion properties between CD28+ and CD28null T cells. Likewise, the adhesion of these T cell subsets was indistinguishable in the presence of exogenous ROS/H2O2. Together, these data provide a molecular explanation of the role of ROS in pathogenesis of plaque destabilization.
Im Titel sind 2+, +, null hochgestellt und 2 tiefgestellt
Gesehen am 23.11.2020